Frizzled receptors signal through G proteins - Nichols, Andrea S. (2013)
Frizzled receptors have long been thought to couple to G proteins but biochemical evidence supporting such an interaction has been lacking. Here we expressed mammalian Wnt-Frizzled fusion proteins in Saccharomyces cerevisiae and tested the receptors’ ability to activate the yeast mitogen-activated protein kinase (MAPK) pathway via heterotrimeric G proteins. Our results show that Frizzled receptors can interact with Gα(i), Gα(q), and Gα(s) proteins, thus confirming that Frizzled functions as a G protein coupled receptor (GPCR). However, the activity level of Frizzled-mediated G protein signaling was much lower than that of a typical GPCR and, surprisingly, was highest when coupled to Gα(s). The Frizzled/Gα(s) interaction was further established in vivo as Drosophila expressing a loss-of-function Gα(s) allele rescued the photoreceptor differentiation phenotype of Frizzled mutant flies. Together, these data point to an important role for Frizzled as a nontraditional GPCR that preferentially couples to Gα(s) heterotrimeric G proteins.